A critical review on various corrosion testing and monitoring techniques - Tan, Yongjun; Lepkova, Katerina; Bailey, Stuart; Gubner, Rolf (Australian Corrosion Association, 2009)
This paper presents a brief review of major corrosion testing and monitoring techniques including corrosion coupons, electrical resistance, electrical field signatures, ultrasonic tests, corrosion potential monitoring, polarisation resistance, electrochemical impedance spectroscopy, electrochemical noise analysis and the wire beam electrode method. Particular focus is on the advantages and disadvantages of these techniques for localised corrosion monitoring in the oil and gas production environment. It is concluded that a major reason that leads to reporting of false corrosion rates and patterns is overlooking localised corrosion mechanisms and their changes with the extension of corrosion tests. Conventional electrochemical methods such as corrosion potential monitoring, polarisation resistance, electrochemical impedance spectroscopy have limitations in measuring localised corrosion. These limitations have to be overcome since surveys have shown that some 70-90% of all corrosion failures are related to localised corrosion. Electrochemical noise analysis and the wire beam electrode method are considered to be the only techniques that have potentials in monitoring localised corrosion. Combination of these two techniques has shown unique ability of not only detecting noise signatures and noise resistance, but also providing unprecedented spatial and temporal information on localised corrosion. Underdeposit corrosion testing is presented as a case to illustrate the importance and difficulties of simulating localised corrosion.